2015
DOI: 10.1007/s10529-015-1858-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a new co-culture system, the “separable-close co-culture system,” to enhance stem-cell-to-chondrocyte differentiation

Abstract: The new co-culture system is effective in terms of assessing gene expression in two cell types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Co‐culture systems have received much attention because in the co‐culture techniques, the stem cells that one wants to differentiate are cultured together with target cells in an effort to promote differentiation due to cellular interactions, such as by trophic effects . Recent literature reported by Kraus et al ., indicated that in direct co‐culture, tenascin C was up‐regulated compared with ADMSCs monoculture, and SCX expression was significantly up‐regulated (1.5‐fold) in the group with an ADMSCs‐to‐tenocyte ratio of 1:3.…”
Section: Discussionmentioning
confidence: 99%
“…Co‐culture systems have received much attention because in the co‐culture techniques, the stem cells that one wants to differentiate are cultured together with target cells in an effort to promote differentiation due to cellular interactions, such as by trophic effects . Recent literature reported by Kraus et al ., indicated that in direct co‐culture, tenascin C was up‐regulated compared with ADMSCs monoculture, and SCX expression was significantly up‐regulated (1.5‐fold) in the group with an ADMSCs‐to‐tenocyte ratio of 1:3.…”
Section: Discussionmentioning
confidence: 99%
“…Cocultures of mesenchymal stem cells and CHDR can result in improved chondrogenic differentiation in pellets [ 9 ] and immunological interactions including anti-inflammatory regulations attributed to mesenchymal stem cells [ 15 ]. The possible high impact of coculture systems on cartilage tissue engineering is documented by the increasing number of described technical solutions [ 16 ] and experimental designs [ 17 ]. In contrast to previous studies, this investigation focused on an experimental trans-well design using human synovial stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently several co-culture models being usedincluding mixed coculture, separated co-culture, and bothto investigate the mechanism of co-culture capable of supporting stable chondrogenesis (Levorson et al 2014;Morita et al 2015). However, overall, the mechanism is still under debate.…”
Section: Co-culture Of Chondrocytes With Mscsmentioning
confidence: 99%